Design and analysis of a 60 GHz high gain wideband magneto electric dipole antenna array based on trapped printed gap waveguide technology - Haitham Hamada; Mohamed Mamdouh M. Ali; Shoukry I. Shams; Ashraf A. M. Khalaf; A. M. M. A. Allam (Scientific Reports)
Abstract This paper introduces an innovative design and analysis of a magneto-electric dipole antenna exhibiting high-gain, ultra-wideband operation, and stable radiation characteristics in the 60-GHz mm-wave band. Furthermore, the trapped printed gap waveguide (TPGW) technology is presented as a low-cost, minimal-loss, and low-dispersion guiding structure to feed the proposed antenna. The antenna covers a relative matching bandwidth of over 33.33% from 50 to 70 GHz with a maximum gain up to 8 dBi. In addition, the antenna is integrated with a perforated dielectric substrate layer lens on the antenna’s broadside location, enhancing the gain by an average of 3 dB along its entire operational bandwidth. Moreover, an efficient approach for designing a large ME dipole antenna array and its corporate feeding network is presented. Both ME-dipole sub-arrays and the out-of-phase power divider with WR-15 standard interface are designed and studied separately, where a systematic design procedure is presented to obtain initial design parameters. A 2 × 2 planar antenna array is designed and implemented, featuring proper integration between the radiating elements and a differentially fed wide-bandwidth TPGW power divider. Then, the operation of the individual components has been assessed using simulation and measurements. Furthermore, an in-depth mathematical analysis is presented to investigate the potential resonance conditions arising from disparities in complementary components. Consequently, a proposed solution is provided to break the resonance loop and shield the two opposing sub-arrays. The 2 × 2 array of ME-dipoles has overall dimensions of 1.6 $$λ _0$$ $$×$$ 1.4 $$λ _0$$ and demonstrates an impedance bandwidth ( $$|S_{11}| <$$ – 10 dB) exceeding 33.33 $$%$$ at 60 GHz, with a peak gain of over 18 dBi.